Hubungan Tingkat Stres Dengan Kecanduan Internet Pada Siswa SMA Negeri 3 Denpasar - Ni Made Widya Apsari Cahyadewi; Ni Wayan Diana Ekayani; Saktivi Harkitasari (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2025)
Teenagers frequently endure stress throughout their transition to adulthood and frequently utilize the internet to cope with it. However, the internet's ease leads to high levels of internet addiction. As a result, this study examined the relationship between stress levels and internet addiction among students at SMA Negeri 3 Denpasar. This study employs an analytical observational method with a cross-sectional design. This study used a stratified random sample technique with the Slovin formula. The sample comprised 268 students who fulfilled the inclusion and exclusion criteria. Data were collected using the Perceived Stress Scale (PSS) and the Internet Addiction Test (IAT) questionnaires. The data will be analyzed bivariate using the SPSS application with the Spearman test method, with the analysis results said to be significant if the p-value is <0.05. The results obtained showed that the majority of respondents experienced moderate stress (61.6%), while the majority experienced moderate internet addiction (45.1%). The Spearman test value obtained was 0.468 with p-value <0,001. This indicates that there is a considerable and reasonably strong association between stress levels and internet addiction. Keywords: stress, addiction, internet, students